A STRATEGY TO IMPROVE THE CONTRIBUTION OF CORAL DATA TO HIGH-RESOLUTION PALEOCLIMATOLOGY - Lough J.M. (My University, 2004)
Various geochemical tracers measured in massive coral skeletons have the potential to compliment other sources of high-resolution proxy climate information (e.g. tree rings, ice cores) by providing paleoclimatic data from shallow-water tropical ocean regions. Twenty previously published coral records (19 δ18O and one Sr/Ca series), between 54 and 346 years in length, were examined for their local and larger-scale relationships (El Niño-Southern Oscillation) with climate. Series were examined in a consistent manner over the same time periods and relationships were tested for stability through time. The results demonstrate a spectrum of climatic interpretation ranging from (1) no significant relationship of the coral record with either local or larger-scale climate variables, (2) significant relationship of the coral record with climate but the relationship is not stable through time, and (3) the coral record shows a significant and temporally stable relationship with climate which explains a significant and useful proportion of climate variance. It is concluded that reliance, to date, on analyzing only one long coral core from a site has prevented identification of coral records or parts of coral records where non-climatic factors are dominating the geochemical signal. Various factors may cause these non-climatic signals to dominate. More process studies into how corals of particular species, with various growth rates and from various environmental settings incorporate geochemical tracers into their skeleton are required to understand exactly what is being measured. In addition, it is recommended that some level of replication (ideally, three separate corals) of geochemical tracers will ensure accurate dating of the record, identification of periods when non-climatic factors dominate and thus enhance the reliability of the paleoclimatic record. Such an approach will allow the rich archive of environmental information contained in massive coral skeletons to make a significant contribution to high-resolution paleoclimatology and improve our understanding of the nature and causes of past climate variability.
Keywords: coral; isotopes; paleoclimate; El Nino-Southern Oscillation; replication; sampling strategy